Product Quality, Celebrity Endorsements, Brand Image, and Trust: Consumer Purchase Decisions - Chandra, Saskia Maharani Putri; Mansur, Amin (Marketing and Business Strategy, 2024)
This research aims to determine the influence of product quality, celebrity endorser, brand image and brand trust on purchasing decisions for Scarlett Whitening products in DKI Jakarta. The population in this research is the entire community. The sampling technique used was a non-probability technique and the number of samples was determined as 100 according to the hair formula. Data was collected using a questionnaire instrument method. The data analysis method used is multiple linear analysis. The results show that (1) product quality has a positive and significant effect on purchasing decisions. (2) celebrity endorsers have a positive and significant effect. (3) partially, brand image has a positive and significant effect. (4) Partially, brand trust has a positive and significant effect on purchasing decisions. The managerial implication of these findings is that companies need to focus on improving product quality, selecting relevant and influential celebrity endorsers, and building and maintaining a strong brand image and trust to maximize consumer purchasing decisions. This research contributes to a deeper understanding of how these factors, particularly in the context of popular celebrity endorsers on social media, may influence consumer purchasing preferences.